2019
DOI: 10.1002/ca.23497
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Anatomy of the Marginal Mandibular Nerve: A Systematic Review and Meta‐Analysis

Abstract: The high number of marginal mandibular nerve (MMN) anatomical variants have a well‐known clinical significance due to the risk of nerve injury in several surgical procedures. The aim of this study was to find and systematize the available anatomical data concerning this nerve. The PubMed and Scopus databases were investigated in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐analyses guidelines. All studies reporting extractable data on the origin, course, splitting, anastomosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…21). A systematic meta-analysis report by Marcuzzo et al [10] reported a prevalence of 30% for MMN originating at the parotid apex and 20% originating at the anterior border of the parotid and established the nerve location relative to the parotid gland. The results suggest that the nerve is above the parotid gland in 76% and below in 18% cases.…”
Section: Surgical Anatomy and Related Considerations Relation To Parotid Glandmentioning
confidence: 98%
See 1 more Smart Citation
“…21). A systematic meta-analysis report by Marcuzzo et al [10] reported a prevalence of 30% for MMN originating at the parotid apex and 20% originating at the anterior border of the parotid and established the nerve location relative to the parotid gland. The results suggest that the nerve is above the parotid gland in 76% and below in 18% cases.…”
Section: Surgical Anatomy and Related Considerations Relation To Parotid Glandmentioning
confidence: 98%
“…Further, Hazani et al [9] proposed that the MMN crosses above the facial artery at about one-fourth distance from the masseteric tuberosity up to mandibular midline and can be used as a reliable landmark for nerve localization. Meta-analysis by Marcuzzo et al [10] concluded that the MMN lies superficial to facial artery in 44% cases when the nerve has multiple branches and 36% cases when a single nerve branch is found. However, they emphasized that the relation to the anterior facial vein (AFV) is more constant and reliable as the nerve lies superficial to AFV in most cases.…”
Section: Relation To Facial Vesselsmentioning
confidence: 99%
“…It then steps over the mandible body and the most anteroinferior fibers of the masseter muscle and finally reaches the chin, where it distributes to the depressor anguli oris, depressor labii inferioris, and mentalis muscles (Figure 1(A)). Several connections between the MMN and regional nerves (e.g., greater auricular, transverse cervical, mental) or other divisions of the facial nerve may be encountered 14,15 …”
Section: Anatomical Considerationsmentioning
confidence: 99%
“…13 The marginal mandibular branch VII (MMB VII) runs along the inferior edge of the mandible, innervating the lower lip muscles (Figure 3). 1,14 These branches are partially cut during the initial skin incision. The quality of anesthesia in carotid endarterectomies could be potentially improved by blocking these nerves.…”
Section: Dovepressmentioning
confidence: 99%
“…7,[10][11][12] Carotid endarterectomies typically involve painful surgical steps, including skin incision involving the dermatomes and the platysma (co-innervation by VII), vessel preparation (carotid plexus innervation: IX, X, ST), and potential retromandibular retractor insertion (co-innervation by V, VII). [7][8][9]13,14 The quality of anesthesia during skin incision is often decisive in regard to further patient comfort.…”
Section: Introductionmentioning
confidence: 99%